1985
DOI: 10.1128/iai.47.1.123-128.1985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antigen form on local immunoglobulin A memory response of intestinal secretions to Shigella flexneri

Abstract: An enhanced memory response, as shown by increased titers of specific immunoglobulin A (IgA), was seen in intestinal secretions from isolated Thiry-Vella loops in rabbits primed orally with live, locally invasive Shigella sp. X16 and challenged 60 days later with a single oral dose of the same antigen. Heat-killed shigella preparations, when used as either the priming or challenge antigen, did not elicit such a memory response in this system. In the present study, the role of antigen form and dosage in eliciti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…We have recently reported that CT significantly enhances the anti-T. gondii secretory IgA response following oral immunization of mice with TSo and CT (2). This enhancement of the intestinal secretory IgA response is of great interest because IgA antibodies have been considered, in some cases, to be protective against oral infection with parasites, bacteria, or viruses (10,24,28). The protective immune response following a primary T. gondii infection is complex and probably involves humoral as well as cellular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that CT significantly enhances the anti-T. gondii secretory IgA response following oral immunization of mice with TSo and CT (2). This enhancement of the intestinal secretory IgA response is of great interest because IgA antibodies have been considered, in some cases, to be protective against oral infection with parasites, bacteria, or viruses (10,24,28). The protective immune response following a primary T. gondii infection is complex and probably involves humoral as well as cellular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have demonstrated intestinal IgA antibodies (1, 7, 16, 17, 26, 28) and milk IgA antibodies (4, 5, 15, 21, 33) following bacterial, viral, or parasitic infection. In some cases, the presence of pathogen-specific IgA antibodies has been associated with protection against infection by the pathogen (2,5,14,17,26,28). McLeod and Mack (23) first demonstrated the production of intestinal IgA antibodies to T. gondii and later suggested that IgA may play a protective role against toxoplasmosis (22).…”
Section: Discussionmentioning
confidence: 99%
“…Various strategies have been employed in attempts to develop vaccines against bacterial enteropathogens such as Shigella, Salmonella, V. cholerae and ETEC, and various degrees of success have been achieved. The approaches differ primarily in the form of antigen chosen for oral administration; i.e., living attenuated strains [5,[9][10][11], whole bacteria killed by either heat and/or chemicals [28,29], purified toxoids to provoke anti-toxin immunity [7,13,14] and purified fimbrial CFAs to provoke immunity against intestinal colonization [12,[16][17]. Candidate vaccines have been designed for each pathogen mainly on the basis of recognized mechanisms of pathogenesis, antigenicity of killed cell preparations or purified virulence factors, and in consideration of the risk of minor but undesirable responses to living attenuated strains.…”
Section: Discussionmentioning
confidence: 99%